PENGARUH PENERAPAN TEKNIK IDENTITAS KORPORAT DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 9 SIJUNJUNG - Astia, Ratna Yulia; Rahmi, Rahmi; Pratiwi, Merina (Pendidikan Matematika, 2013)
The research was due to the fact that most students were not used to have a discussion and share knowledge with the peers. Moreover, they had lack of understanding mathematical concept which could be seen from the mathematic result of grade VII students SMPN 9 Sijunjung. The research aimed at describing students activities and understanding how far the students of grade VIII SMPN 9 understood the mathematic concept using corporate identity technique with a quiz, whether it was better than conventional learning. The design was experimental research using random sampling technique. The population was students of grade VIII SMPN 9 Sijunjung. Based on the result of random sampling technique, grade VIII2 was chosen as the experimental group, while the grade VIII3 as the control group. The instrument used was observation sheet and essay mathematic test. The reliability of the test was . Based on the analysis of observation sheet, there was an improvement of students activities during the teaching and learning process and the data analysis obtained was distributed homogeny and normal. The technique analysis data used was one way t test. Based on the analysis of hypothesis using MINITAB, it was obtained that the p-value was less than . Therefore, it can be concluded the student understanding of mathematical concept using corporate identity technique with a quiz was better than conventional learning at grade VIII SMPN 9 Sijunjung.